The impact of the development of industrial democracy on the level of labor protection in Kazakhstani organizations in the conditions of the economic crisis (Journal of actual problems of jurisprudence, 2021)
Currently, a situation has emerged when making the most important decisions directly related to employees is an inalienable prerogative of the employer. And this at a time when in foreign countries there was an effective system of employee participation in the management of an organization, which directly leads to an increase in the efficiency of labor protection. The aim of the work is to identify the nature of the influence of the level of development of elements of industrial democracy on the effectiveness of labor protection and personnel management in Kazakhstani organizations. The article provides a literary review of scientific research devoted to the impact of industrial democracy on the level of protection of workers’ rights in an organization. The results of the author’s research of this issue in Kazakhstani organizations operating in crisis conditions are also presented. The economic crisis, as a rule, leads to a reduction in the personnel of organizations in violation of labor legislation, which increases the reliability of the results obtained. The methodology consists in a questionnaire survey of employees of Kazakhstani companies on the development of elements of industrial democracy, division into two groups (with the absence of elements of industrial democracy and with the presence) and a comparative analysis of labor protection indicators in the context of the economic crisis. As a result of the study, the relationship was determined and the hypothesis that the elements of industrial democracy have a positive effect on the practice of labor protection was confirmed. The practical value lies in creating an evidence base for starting the implementation of projects for the development of industrial democracy at both the macro and micro levels. The results can be used as a substantiation of legislative initiatives for the development of the legal framework of industrial democracy in the Republic of Kazakhstan.Key words: labor relations, workers’ rights, industrial democracy.